ANALISIS KEMAMPUAN LITERASI NUMERASI MELALUI SOAL CERITA DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI SDN CANDIPARI 2 PORONG - Sahrina, Alfi; Muhammad Yusron Maulana El-Yunusi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One of the factors that causes a decrease in student learning outcomes is because students' reading skills can only work on questions that are easy to understand. From these results, efforts are needed to improve the quality of education to build students' interest in reading, so the school literacy movement at the elementary school level is very important. Numeracy literacy is one thing that is useful for training students to think and reason intelligently. Critical. This research aims to analyze numeracy literacy abilities, and to analyze the critical thinking abilities of class V B students. The research method used in this research is descriptive research using a qualitative approach. The subjects of this research were students in class V B at SDN Candipari 2 Porong. The data collection method in this research involves students working on essay test questions, then researchers conducting interviews. The results of this research show that when students solve story problems based on numeracy literacy, they show good results, and students' critical thinking skills in solving numeracy literacy questions on story problems also show good results.